Driving innovation : intellectual property strategies for a dynamic world - Gollin, Michael A., 1957- (Cambridge ; New York : Cambridge University Press, 2008)
How does IP balance the exclusive rights of innovators with public demand for access to their innovations? How can organizations manage IP strategically to meet their goals? How do IP strategies play out on the global stage? Driving Innovation reveals the dynamics of intellectual property (IP) as it drives the innovation cycle and shapes global society. The book presents fundamental IP concepts and practical legal and business strategies that apply to all innovation communities, including industry, non-profit institutions, and developing countries. Further, it draws on the author's broad experience, news headlines, and precedent-setting lawsuits relating to patents, trademarks, copyright, and trade secrets - from biotechnology to the open source movement. General readers and students will welcome the lively overview of this complex topic, while executives and practitioners can gain new insights and valuable approaches for putting ideas to work and navigating within or changing the global IP system to expand innovation.
The innovation cycle and creative destruction -- The rise of the intellectual property system -- Creative tension : the right to exclude and the accessible domain -- The innovation forest : intellectual property rights and how they grow -- The ABCDs of intellectual property : flow and infringement of IP rights -- The global diversity of innovation communities -- The role of the innovation chief -- Becoming strategic -- Strategy tools : policies and practices for managing IP -- A menu of strategy options -- Evaluating internal resources and the external environment -- Placing a financial value on IP assets -- Accessing innovations of others -- Protecting and enforcing IP rights -- Transferring IP rights -- IP strategies for different organizations -- A comparison of national IP laws -- Global challenges and opportunities -- Intellectual property, innovation, and freedom.
Includes bibliographical references (pages 379-389) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Intellectual property; Propriété intellectuelle; intellectual property; LAW -- Business & Financial; LAW -- Intellectual Property -- General; Intellectual property; Geistiges Eigentum; Electronic book; Electronic books